HUBUNGAN MASA KERJA DENGAN KADAR KOLINESTERASE DALAM DARAH PETANI DI DESA PASIRHALANG, CISARUA, KABUPATEN BANDUNG BARAT - Gita Nur Fajriani; Suci Rizki Nurul Aeni; Viky Cahyo Handoko (Klinikal Sains : Jurnal Analis Kesehatan, 2019)
Development in agricultural field can not be separated from pesticides, used to eradicate pests. Continuely use by farmer caused poisoning, that can be measured by cholinesterase levels in blood. This research tried to identify correlation between work period and cholinesterase level in farmer’s blood. Research was carried using cross sectional method with 43 farmers from Desa Pasirhalang Kecamatan Cisarua, Kabupaten Bandung Barat. Farmer’s work periods were 51,2% that have work more than 15 years and 48,8% that have work less then 15 years. Poisoning levels were 14% severe poisoning (50 – <75% cholinesterase level) and 86% normal (75 - 100% cholinesterase levels). Correlational statistic using Spearman test showed that there was no significant correlation between work period and cholinesterase levels in farmer’s blood.